(untitled) (MAUSAM, 2022)
An analysis was carried out to study the rainfall variability and its probability for different categories of rainfall events (2.5-25, 25-50, 50-75, 75-100 and >100 mm) in Punjab during the period (1971-2011). The rainfall showed decreasing trend in Ludhiana, Roop Nagar, Hoshiarpur and Ferozpur representing different agroclimatic zones of the state. The probability of rainfall at different level of significance (90, 75, 50, 25, 10%) was computed and it was found that the highest probability rainfall was observed at 10% level and lowest rainfall probability was observed at 90% level of confidence. The study of drought indicated that the frequencies of drought were reported 4 times in Faridkot, 4 times in Mukatsar, 3 times in Ludhiana, 3 times in Sangrur and 3 times in Moga.